Depression in patients with multiple sclerosis. The prevalence, diagnostic challenges and evidence-based treatment methods - Wegenko, Cezary Michał; Sitka, Hanna; Czaja, Magdalena; Kuźniar, Julia; Kozubek, Patrycja (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Gradual progression of cognitive and physical disability negatively affects personal, social and economic well-being of patients with multiple sclerosis. This particular group of people has a high risk of developing depressive disorders. This study reviews the prevalence, current diagnostic tools and evidence-based methods of treating depression in patients suffering from MS. Material and Methods: This paper reviews various types of research documents with a special focus on sources from the past 10 years. Works from the 1980s and 1990s were also cited to outline the progress made in exploring the given topic. Its main aim is to indicate that MS poses a risk of developing depression and to emphasize that this disorder may be mistakenly attributed to the primary disease. It highlights the need for raising awareness about the topic to ensure interdisciplinary care. Results: The study proved the connection between the prevalence of depression in MS. Characteristic somatic depressive symptoms such as chronic fatigue, sleep disturbances, can conclude either from MS or depression. Because of that prevalence of depression in MS patients is artificially altered. Conclusion: The prevalence of depression is significantly greater in patients with multiple sclerosis compared to the general population. Many somatic symptoms caused directly by neurodegenerative changes pose difficulties in differential diagnosis. Multidisciplinary treatment, including both psycho- and pharmacotherapy, remains the most effective therapeutic approach. Nevertheless, the development of new, accurate diagnostic methods is necessary in order to screen for depression in this group of patients.